Anticonvulsant Activity of Flower Part of N.Oderum - POOJA SAINI; N. KANNAPAN; ANUPAMA DIWAN; PARVEEN KUMAR; VISHAL ANTIL; SHREYA SHARMA; SANDEEP SINGH (International Journal of Pharma and Bio Sciences, 2010)
Different extracts (Petroleum ether, methanolic, aqueous) of Nerium oderum at a dose level of 400 mg/kg were screened for the anticonvulsant activity using Maximum Electroshock Induced Seizures & Pentylene Tetrazole Induced Seizures test models. From the present study, Petroleum ether extract of N. oderum showed better anticonvulsant activity as compared to other extracts.